Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Tanaman Hias Sukulen di Cactiae Kota Semarang - Worang, Deangelo Revano; Setiyawan, Hery; Budiraharjo, Kustopo (Universitas Galuh, 2025)
ABSTRACTThis research was conducted in September-October 2024 at Cactiae, Semarang City. The objective of this research is to determine the characteristics of succulent plant consumers and to analyze the influence of the marketing mix, including product, price, distribution, promotion, process, people, and physical evidence, on the purchasing decisions of succulent plants at Cactiae, Semarang City. The research location was purposively selected due to the declining sales problem at Cactiae, Semarang City. The research method used was a case study. The sampling method used was accidental sampling with a total of 208 respondents. The respondents' criteria were consumers who had purchased succulent plants at Cactiae, Semarang City at least once online. Data collection was conducted online by distributing QR codes that directed respondents to fill out a questionnaire through Google Forms. The data used were primary and secondary data. The data analysis methods used were descriptive analysis and multiple linear regression analysis. Multiple linear regression analysis was conducted using SPSS 26.0. The results of this study show that the majority of consumers at Cactiae, Semarang City are female, have a bachelor's degree, are aged 21-30 years, work as private employees, and have 4-6 family members. The marketing mix aspects, including product, price, distribution, promotion, process, people, and physical evidence, have a simultaneous influence on purchasing decisions. The marketing mix aspects, including distribution, process, and people, have a partial influence on purchasing decisions. The coefficient of determination is 28.6%.